Documentation of a new intracavitary applicator for transrectal hyperthermia for prostate cancer cases. (September 2016) - Nikolakopoulou, A.; Armpilia, C.; Antypas, C.; Karanasiou, E.; Avgousti, R.; Apostolou, E.; Uzunoglou, N.; Gogalis, I.; Kouloulias, V.
Abstract : Introduction: A new intracavitary microwave hyperthermia applicator specially designed for heating prostate through the rectal is designed. The aim of this study is to document the new antenna operating at 433 MHz, as well as to assess the SAR distributions in terms of thermometry in a soft tissue phantom. Materials and methods: The microwave applicator consists of a dipole-type l/2, a reflector and a cooling liquid. To evaluate the SAR distribution the applicator was inserted into the gel-phantom box that mimics the dielectric properties of the normal tissue. The applicator is connected to the power unit to generate the electromagnetic field, which propagates across the antenna. The temperature distribution is detected with a calibrated thermometer, which is implanted into specific locations of the phantom. Results: The maximum value of the SAR is found on the surface's central area of the antenna, located into the phantom box. The penetration depth of microwaves, defined as the depth at which the rate of SAR is the half of the maximum rate measured at the surface of the antenna, was calculated to be 3 cm. Our measurements confirm the role of the reflector to direct the microwaves towards in a certain area in contrast to other treatment devices which direct SAR distribution symmetrically. Conclusion: The 2-D SAR characteristics of a new designed applicator were investigated. Our experimental measurements showed that it can be used effectively as a treatment device for prostate cancer demonstrating a clear advantage of other similar devices.